Effects of diaphragmatic control on multiparametric analysis of the sniff nasal inspiratory pressure test and inspiratory muscle activity in healthy subjects. - Kadja Benício (Public Library of Science (PLoS), 2021)
Background We investigated the influence of diaphragmatic activation control (diaphC) on the relaxation rate, contractile properties and electrical activity of the inspiratory muscles of healthy subjects. Assessments were performed non-invasively using the sniff inspiratory pressure test (SNIP) and surface electromyography, respectively. Methods Twenty-two subjects (10 men and 12 women) performed 10 sniff maneuvers in two different days: with and without diaphC instructions. For the SNIP test with diaphC, the subjects were instructed to perform intense activation of the diaphragm. The tests with the best SNIP values were used for analysis. Results The maneuver with diaphC when compared to the maneuver without diaphC exhibited significant lower values for: SNIP (p <0.01), maximum relaxation rate (MRR) (p <0.01), maximum rate of pressure development (MRPD) (p <0.01), contraction times (CT) (p = 0.02) and electrical activity of the sternocleidomastoid (SCM) (p <0.01), scalene (SCL) (p = 0.01) and intercostal (CI) (p = 0.03) muscles. In addition, the decay constant (tau, τ) and relaxation time (½ RT) did not present any changes. Conclusion The diaphragmatic control performed during the SNIP test influences the inspiratory pressure and the contractile properties of inspiratory muscles. This occurs due to changes in the pattern of muscle recruitment, which change force velocity characteristics of the test. Thus, instruction on diaphC should be encouraged for better performance of the SNIP test and for evaluation targeting the diaphragm muscle activity.